Assessment of commuters' perception of jeepney transit service quality and the potential for an introduction of point-to-point e-tricycle transport service in UP Diliman - Cabatos, Lawdemhar T.
This study aims to determine the commuter perception of existing service quality of jeepney transit in UP Diliman. Critical service gaps are determined and priority service parameters for rehabilitation are identified. Results of the commuter perception study are used to design a new mode of transport, in the form of a point-to-point (P2P) e-tricycle service, with due consideration of the critical service gaps earlier identified. The SERVQUAL method is used to determine commuter perception and satisfaction of existing jeepney transport. The BEMAC e-tricycle is presented as the proposed new alternative mode of transport. Physical and online surveys are conducted using the Stated Preference (SP) survey. Survey results showed a positive perception of all service parameters of the Ikot service, while a negative perception of a few parameters of the Toki service. The Ikot and Toki were rated overall as 'Good to Very Good and 'Good', respectively. Results of the stated preference survey also showed a huge shift in mode shares of the jeepney upon the introduction of the P2P service, from 88.43% to 44.51%, while the P2P service had a mode share of 46.88%.